2018
DOI: 10.1021/acsphotonics.8b01312
|View full text |Cite
|
Sign up to set email alerts
|

Ultraintense Femtosecond Magnetic Nanoprobes Induced by Azimuthally Polarized Laser Beams

Abstract: We report a novel scheme to generate laser-induced, ultrafast, intense (Tesla scale), spatially isolated, magnetic fields. Three-dimensional particle-in-cell simulations show that a femtosecond azimuthally-polarized infrared vector beam, aimed to a conducting circular aperture, produces an intense axially polarized tip-shaped femtosecond magnetic field, extending over micrometer distances and being isolated from the electric field. Our results are backed-up by an analytic model, demonstrating the underlying ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…Such XUV beams with controlled angular momenta can also be used to enhance light microscopy -through high-contrast high-resolution spiralphase imaging [65] or XUV microscopy [16] -, in lithography [66], and as tailored waveforms for developing and improving spectroscopic techniques [67,68]. Finally, we note that TKAM conservation in HHG provides a new tool to study ultrafast magnetism, in particular to image magnetic domains [69], to uncover spin/charge dynamics in magnetic materials [70] and to generate ultrafast magnetic fields [71]…”
mentioning
confidence: 99%
“…Such XUV beams with controlled angular momenta can also be used to enhance light microscopy -through high-contrast high-resolution spiralphase imaging [65] or XUV microscopy [16] -, in lithography [66], and as tailored waveforms for developing and improving spectroscopic techniques [67,68]. Finally, we note that TKAM conservation in HHG provides a new tool to study ultrafast magnetism, in particular to image magnetic domains [69], to uncover spin/charge dynamics in magnetic materials [70] and to generate ultrafast magnetic fields [71]…”
mentioning
confidence: 99%
“…First of all, we observe that the electrons’ response time delays the magnetic pulse by about 4 fs with respect to the optical pulse. We can then see that the decay of the magnetic pulse is slower than that of the optical pulse due to both the relaxation time of the electrons in gold , and the relaxation time of the energy within the structure. Finally, while the optical pulse’s peak power is the same as during the search for an optimal structure by the GA, the magnetic field B created by the antenna reaches a value of only about 1.5 T. The decay of the optical pulse stops the acceleration of the electrons before reaching their full speed.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, we have demonstrated that the recently developed scenario of spatially isolated femtosecond B-fields [26][27][28][29] opens the path to the ultrafast manipulation of magnetization dynamics by purely precessional effects, avoiding the heating due to the E-field or magnetization damping. Our numerical results already demonstrate that all-optical switching at the fs time scale can be achieved with circularly polarized B-fields of 275 T. However, we believe that our work paves the way towards all-optical switching at even shorter timescales, towards the attosecond regime.…”
mentioning
confidence: 99%
“…In this regard, the recent generation of spatially isolated fs magnetic fields (B-fields) opens the possibility to induce magnetization dynamics solely by the interaction with an ultrafast B-field, thus neglecting the E-field. In particular, azimuthally polarized fs laser beams have been demonstrated to induce large oscillating currents on circular apertures that, in turn, produce a Tesla-scale fs B-field, spatially isolated from the E-field [26][27][28][29]. Previously, azymuthally-polarized on-axis laser beams were used to induce mili-Tesla static B-fields [30], with applications in nanoscale magnetic excitations and photoinduced force microscopy [31,32].…”
mentioning
confidence: 99%